Puntos diana como localizaciones para la realización de encuestas: Índice de Potencialidad Turística de la provincia de Burgos; Target points as survey locations: Touristic Potentiality Index of the Burgos province - Santiago Aparicio Castillo; Pablo Arranz Val; Arturo Alvear González; Paula Antón Mara\~na; Julio César Puche Regaliza (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– This work analyzes an inventory of the touristic resources of the province of Burgos (Spain) and identifies with it the municipalities with the greatest touristic attraction, thus identifying the target points that facilitate the planning of the fieldwork process to obtain the opinion of tourists. To provide an analytical approach, this study adopts a quantitative technique by constructing a weighted synthetic index following a hierarchical process. The results show that the province of Burgos stands out for its high natural or landscape heritage, with access through minor roads and with a high offer of hotels and rural houses as well as restaurants and cafeterias. Fairs declared of interest, access by rail and the offer of hostels, apartments and campsites offer fewer outstanding values. The work proposes the realization of around 383 observations in each of the eight target points identified. The results obtained are clear enough to motivate decision-makers to address their efforts and investments in improving and adjusting their strategies to increase the quality of offer and demand in the touristic sectors.
Keywords: C42; C43; L83; 330; Touristic Potentiality Index; Target Points; Survey Locations; Touristic Resources; Province of Burgos